Korelasi Antara Intensitas Doomscrolling Konten Negatif Kehamilan di Media Sosial dengan Tingkat Stres dan Kecemasan Ibu Hamil - AM, Besse Aismaria; Eppang B, Yudiarsi; C, Jusniati (UI Scholars Hub, 2025)
Background.The rapid development of social media has significantly influenced information-seeking behavior, including among pregnant women. One emerging phenomenon is doomscrolling, defined as the excessive consumption of negative information, which may trigger stress and anxiety. Aim. This study aimed to analyze the correlation between the intensity of doomscrolling of negative pregnancy-related information on social media and levels of stress and anxiety among pregnant women in Pare-Pare City. Method. This study employed a quantitative method with a cross-sectional design. The study population consisted of all pregnant women attending antenatal care at public health centers in Pare-Pare City, with a sample of 40 respondents selected using the Slovin formula. Data were collected using a doomscrolling intensity questionnaire, the Perceived Stress Scale (PSS-10), and the Generalized Anxiety Disorder scale (GAD-7). Data analysis was conducted using univariate and bivariate analyses with the Kendall’s tau-b test. Result. Research shows that 42.5% of respondents have a moderate intensity of doomscrolling, 52.5% of res-pondents have a moderate level of stress, and 50% of respondents have a moderate level of anxiety. Statistical tests show a significant correlation between the intensity of doomscrolling and stress levels (p=0.004) and anxiety (p=0.002). Conclusion. Doomscrolling is correlated with the mental well being of pregnant women therefore, improvements in digital literacy and psychological support provided by healthcare professionals are needed.